Detection of physiological and genotoxic damages reflecting toxicity in Kalanchoe clones - ÖZYİĞİT, İBRAHİM İLKER (My University, 2016)
In order to make assessments in understanding of physiological and genotoxic effects of imposing cadmium (Cd) on photosynthetic pigment contents along with the changes occurring in genetic material of Kalanchoe plants were used in relation to various Cd-treatments. Young plantlets were originated from a single host plant as clones, and developed in vitro. Developed clones were grown in standard pots with daily watering of Hoagland solution (20 ml) containing different concentrations of cadmium chloride for two months. Cd concentrations of the collected samples were measured by employing ICP-OES and RAPD-PCR technique was applied for detecting the genotoxic effects of Cd. After two month of experimental period, the comparisons between unexposed and exposed Kalanchoe clone groups revealed reductions in photosynthetic pigment contents, especially at the highest level of Cd exposure and a genomic instability when application of Cd concentration increases. RAPD-PCR analyses demonstrated the distinguishable banding pattern in number and band intensities between Cd-treated and control groups. In addition, progressive Cd accumulations in leaves, stems and roots of plant samples were observed when the application of exposure level increased.